EFFECTIVENESS OF SANCTIONS IN IMMIGRATION LAW ENFORCEMENT: ON VIOLATIONS OF RESIDENCE PERMITS BY FOREIGN NATIONALS IN INDONESIA THROUGH A PROGRESSIVE LAW APPROACH - Hutagalung, Gabryela Stevy (Journal of Studia Legalia, 2025)
This study aims to analyze the justice and effectiveness of sanctions in the enforcement of immigration law against the misuse of residence permits in Indonesia. The misuse of residence permits by foreign nationals reflects challenges in achieving an immigration system that is fair, efficient, and consistent with the goal of protecting national sovereignty. This research employs a normative juridical method with statutory and conceptual approaches, based on Law Number 63 of 2024 on Immigration, as well as its relation to Law Number 11 of 2020 and Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation. The findings indicate that the enforcement of immigration sanctions remains dominated by a formalistic criminal approach, which has not yet reflected the principle of substantive justice as articulated in Satjipto Rahardjo’s theory of progressive law. An overly textual interpretation of residence permit violations tends to produce inefficiency and disproportionality in legal responses. Therefore, reformulation of immigration policies is required to emphasize proportionality, enforcement efficiency, and the prioritization of administrative measures as the primary instrument for fair and effective immigration law enforcement.